2022
DOI: 10.1186/s13047-022-00558-z
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for a randomised, assessor‐blinded, parallel group feasibility trial of flat flexible school shoes for adolescents with patellofemoral pain

Abstract: Background There are limited evidence-based treatment options for adolescents with patellofemoral pain (PFP). Flat, flexible footwear have been shown to reduce patellofemoral joint loading and pain in adults with PFP. The efficacy of this intervention in adolescents with PFP is not established. The primary aim of this study is to determine the feasibility of conducting a large-scale randomised controlled trial (RCT) of the effect of flat, flexible school footwear, when compared to traditional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 82 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…The research was developed and is reported according to the Standard Protocol Items: Recommendations for Interventional Trials 2013 statement17 and the Consolidated Standard of Reporting Trials 2010 guidelines for randomised pilot and feasibility trials 18. The published protocol for this feasibility trial provides a detailed account of the methodology 19…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The research was developed and is reported according to the Standard Protocol Items: Recommendations for Interventional Trials 2013 statement17 and the Consolidated Standard of Reporting Trials 2010 guidelines for randomised pilot and feasibility trials 18. The published protocol for this feasibility trial provides a detailed account of the methodology 19…”
Section: Methodsmentioning
confidence: 99%
“…Secondary self-reported outcome measures were collected at baseline, 6 weeks and 12 weeks via Qualtrics. Further detail of each outcome measure are provided in the published protocol 19. In brief, secondary outcome measures included: (1) usual and worst pain severity over the past week using an 11-point numeric rating scale (minimal clinically important difference (MCID) =1.2 points)25 26; (2) all subscales of the Knee Injury and Osteoarthritis Outcome Score Child (KOOS-Child) (MCID=14.6–22.6 points)27; (3) Knee Injury and Osteoarthritis Outcome Score Patellofemoral (KOOS-PF) (MCID=16.4 points)28; (4) Anterior Knee Pain Scale (AKPS) (MCID=10 points)26 29; (5) Youth Quality of Life Short Form30 and (6) Global Rating of Change 31…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation